2012
DOI: 10.1016/j.neuropharm.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Altered cerebellar organization and function in monoamine oxidase A hypomorphic mice

Abstract: Monoamine oxidase A (MAO-A) is the key enzyme for the degradation of brain serotonin (5-hydroxytryptamine, 5-HT), norepinephrine (NE) and dopamine (DA). We recently generated and characterized a novel line of MAO-A hypormorphic mice (MAO-ANeo), featuring elevated monoamine levels, social deficits and perseverative behaviors as well as morphological changes in the basolateral amygdala and orbitofrontal cortex. Here we showed that MAO-ANeo mice displayed deficits in motor control, manifested as subtle disturbanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 91 publications
(107 reference statements)
0
6
0
Order By: Relevance
“…Similar to Maoa KO mice, Maoa Neo mice display impairments in social behavior, as well as communication deficits and perseverative behaviors (Bortolato et al, 2011 and unpublished data). In addition, we found that these animals feature alterations in their cerebellar morphology (Alzghoul et al, 2012) reminiscent of abnormalities documented in autism-spectrum disorder patients. In contrast with KO mice, however, their Maoa Neo counterparts display no spontaneous aggression, affording a unique experimental platform to test the effects of early adversities on the development of this trait.…”
Section: Role Of Maoa Allelic Variants In the Ontogeny Of Aggressionmentioning
confidence: 59%
“…Similar to Maoa KO mice, Maoa Neo mice display impairments in social behavior, as well as communication deficits and perseverative behaviors (Bortolato et al, 2011 and unpublished data). In addition, we found that these animals feature alterations in their cerebellar morphology (Alzghoul et al, 2012) reminiscent of abnormalities documented in autism-spectrum disorder patients. In contrast with KO mice, however, their Maoa Neo counterparts display no spontaneous aggression, affording a unique experimental platform to test the effects of early adversities on the development of this trait.…”
Section: Role Of Maoa Allelic Variants In the Ontogeny Of Aggressionmentioning
confidence: 59%
“…Similarly, early exposure of rats to MAO inhibitors (both MAO-A and B), throughout development has been shown to produce increase in impulsivity, stereotypic behavior and seizures (Whitaker-Azmitia et al 1994). Further, altered cerebellar organization and function has been reported in MAO A hypomorphic mice (Alzghoul et al 2012). On a similar line, rats exposed prenatally to the serotonin reuptake inhibitor cocaine show less interactions in social interaction tasks as juveniles and adults and exhibit impaired ability to sustain attention (Overstreet et al 2000; Gendle et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Cerebellum has been implicated in catecholaminergic dysfunction. Mice generated with decreased levels of monoamine oxidase A (MAO-A), an enzyme integral to maintaining normal catecholamine levels, exhibit smaller cerebellums, decreased Purkinje cell count and dendritic density, and vermal hypoplasia (Alzghoul et al, 2012 ). MAO-A/B knockout mice also show enhanced eye-blink conditioning, which depends on cerebellar integrity, suggesting another critical cerebellar process contingent on catecholaminergic signaling (Singh et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%